Effect of light sources and curing mode techniques on sorption, solubility and biaxial flexural strength of a composite resin - Andreia Assis Carvalho; Francine do Couto Lima Moreira; Rodrigo Borges Fonseca; Carlos José Soares; Eduardo Batista Franco; João Batista de Souza; Lawrence Gonzaga Lopes (University of São Paulo, 2012)
Adequate polymerization plays an important role on the longevity of the composite resin restorations. OBJECTIVES: The aim of this study was to evaluate the effect of light-curing units, curing mode techniques and storage media on sorption, solubility and biaxial flexural strength (BFS) of a composite resin. MATERIAL AND METHODS: Two hundred and forty specimens were made of one composite resin (Esthet-X) in a stainless steel mold (2 mm x 8 mm Ø), and divided into 24 groups (n=10) established according to the 4 study factors: light-curing units: quartz tungsten halogen (QTH) lamp and light-emitting diodes (LED); energy densities: 16 J/cm² and 20 J/cm²; curing modes: conventional (CM) and pulse-delay (PD); and permeants: deionized water and 75% ethanol for 28 days. Sorption and solubility tests were performed according to ISO 4049:2000 specifications. All specimens were then tested for BFS according to ASTM F394-78 specification. Data were analyzed by three-way ANOVA followed by Tukey, Kruskal-Wallis and Mann-Whitney tests (α=0.05). RESULTS: In general, no significant differences were found regarding sorption, solubility or BFS means for the light-curing units and curing modes (p>0.05). Only LED unit using 16 J/cm² and PD using 10 s produced higher sorption and solubility values than QTH. Otherwise, using CM (16 J/cm²), LED produced lower values of BFS than QTH (p<0.05). 75% ethanol permeant produced higher values of sorption and solubility and lower values of BFS than water (p<0.05). CONCLUSION: Ethanol storage media produced more damage on composite resin than water. In general the LED and QTH curing units using 16 and 20 J/cm² by CM and PD curing modes produced no influence on the sorption, solubility or BFS of the tested resin.